Comparison alpacas embryos cultivation systems - Pérez Durand, Manuel Guido (2017)
The present study was carried out in a laboratory of Animal Reproduction of the Faculty of Veterinary Medicine and Animal Science of the National University of the Puno-Peru Highland. The main objective was to evaluate the effect of in vitro and in vivo culture of alpacas zygotes produced in vitro. We used 226 cumulus oocyte complexes (CCOs), which were obtained from the ovaries from animals that were beneficiated in the camal and transported in 0.9% saline and supplemented with antibiotics. CCOs were aspirated from follicles of 2 to 6 mm. The oocytes were matured in TCM 2520, supplemented with 2.2 mg/mL with sodium bicarbonate, 0.0028 mg/mL sodium pyruvate, 10% fetal serum, 2 IU/mL equine chorionic gonadotropin, 10 IU/mL chorionic gonadotropin Human plus 50 ug/mL gentamicin and were cultured at 38.5°C, under 5% CO2, and high humidity for 36 h. Fertilization was performed in FERT TALP (10 oocytes/drop). For the in vitro culture SOFaa was used. In vivo culture was used oviduct of females. The results were: At 120 h of culture in vitro post insemination, 19 (17.4%) morulae and 8 (7.3%) blastocytes were observed and at 168 h, 18 (16.5%) morulae and 7 (6.4%) blastocytes were observed. From the in vivo culture in the oviduct of the receiving alpacas 3 blastocytes hatched, 5 blastulas and 2 collapsed blastulas were recovered. Conclusion The in vitro and in vivo culture of the zygotes produced in vitro is possible to be used for the production of alpaca embryos.